Reactions of Cobaloxime with Substituted Styrenes - TABATABAEIAN, K.; MAMAGHANI, M.; KESHAVARZ, E.; KHORAMIAN, F. (Asian Journal of Chemistry, 2010)
Alkenes (2a-c) reacted with N-bromosuccinimide and 2-propynol in dichloromethane at -30ºC and formed an oily mixture of regioisomeric (3a-c, 4a-c). Isomers (3a-c) which were the main products formed oxolanes (5a-c) in the presence of cobaloxime. The oxidation of (5a-c) with excess CrO3.py in dichloromethane produce α-methylene-γ-butyrolactone (7a-c).